Lexical Richness in English Language and Culture Department Students’ Undergraduate Theses - Suwarni Wijaya Halim (Journal of English Language and Culture, 2018)
The objective of this research is to find out the lexical richness that the students of English Language and Culture Department have by deeply analyzing their undergraduate theses as the data. The researcher limited the data into undergraduate theses produced by students of batch 2010/2011 of English Language and Culture Department. The researcher used computer software called AntWordProfiler, a kind of software for profiling texts created by Laurence Anthony. The data were processed using the said software in order to produce the type and the token of the text. Afterwards, the researcher used type-token ratio (TTR) as the method in measuring the lexical richness as a part of data analysis. The closer the TTR score to 1, the higher the lexical richness is. However, the result shows that the students’ lexical richness is quite low since none of the students achieved even 0.5.Keywords:  lexical richness, type-token ratio (TTR), undergraduate theses